Correlation Analysis Between Hyperbaric Oxygen Therapy and Quality of Sleep - ivana, stacey; fatoni, patmah; kusumawati, lucia (Liaison Journal of Engineering, 2024)
A good sleep quality and quantity is essential to achieve a healthy body and mind. Hyperbaric oxygen therapy (HBOT) is a treatment involving a specialized chamber where pressure and pure oxygen will be supplied, which can influence inflammation, oxidative stress, cortisol, and melatonin, which may influence sleep quality. Therefore, the purpose of this study is to identify if there is a significant and positive correlation between hyperbaric oxygen therapy and sleep quality. In this study, participants’ sleep quality is assessed by Pittsburgh Sleep Quality Index before and after undergoing HBOT treatment. The participants are also divided into 5 groups based on the number of HBOT treatment that they have undergone. The result of this study is that there is a significant positive correlation between hyperbaric oxygen therapy and sleep quality (p-value<0.001), along with sleep quantity (p-value<0.001). And subjects can acquire the best sleep quality after more than 41 hyperbaric oxygen therapy at 3 ATA (p-value <0.07). Keywords: Hyperbaric Oxygen Therapy; Sleep Quality; Sleep Quantity; PSQI